2009
DOI: 10.1007/s10681-008-9865-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of molecular markers linked to fertility restorer gene(s) for WA-CMS lines of rice

Abstract: The present study was carried out with the objective to validate the molecular markers, which have been previously reported to be linked to fertility restorer (Rf) gene(s) for WA-CMS lines of rice. Two mapping populations involving fertility restorer lines for WA-cytoplasm, viz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 16 publications
4
38
0
Order By: Relevance
“…The hybrids produced using converted Swarna breeding lines with Rf3 gene showed 15-20% of more pollen and spikelet fertility than the partial restorer Swarna. This clearly demonstrates that that Rf3 gene may be contributing 15 to 30% for the fertility restoration trait of WA-CMS and Rf4 may be contributing about 70% for the same trait and presence of both the genes can bestow complete fertility restoration 13,[33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…The hybrids produced using converted Swarna breeding lines with Rf3 gene showed 15-20% of more pollen and spikelet fertility than the partial restorer Swarna. This clearly demonstrates that that Rf3 gene may be contributing 15 to 30% for the fertility restoration trait of WA-CMS and Rf4 may be contributing about 70% for the same trait and presence of both the genes can bestow complete fertility restoration 13,[33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Nas et al (2003) demonstrated the use of molecular markers for identification of restorer line. The usefulness of RM6100 in marker aided selection of restorer with selection accuracy of 97% and 94.87% was reported by Singh et al (2005) and Sheeba et al (2009) respectively. Revathi et al (2013) indicated that molecular screening for fertility restoration can be a useful tool for identifying restorers from breeding lines of unknown restoration status with 80 to 85% efficiency without making and evaluating large number of tedious test crosses.…”
Section: Discussionmentioning
confidence: 79%
“…Of several rice microsatellite and EST-based STS markers used, the RM6100 marker was found to be tightly linked to the flanking Rf4 gene. Sheeba et al (2009) also validated its tight linkage with the WA-CMS fertility restorer in two mapping populations, and this marker was located at a distance of ~1.2 cM. However, molecular screening Table 2 Summary of the genotyping assay and accuracy predicted at Rf4 locus with both of A/C single nucleotide polymorphism (SNP)-based kompetitive allele specific PCR (KASP) and simple-sequence repeats (SSR) markers of RM6100…”
Section: Discussionmentioning
confidence: 99%